The Effectiveness of Rosetta Stone as Media to Increase Vocabulary Skill in EFL Senior High School - Debataraja, Christina Suriani; Daulay, Sholihatul Hamidah (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2024)
Speaking skills in English can be obtained by mastering vocabulary. Therefore, this research aims to identify the improvement of students' mastery of vocabulary after utilizing Rosetta Stone. This study gathered both quantitative and qualitative data. The research was conducted on 20 purposively selected first-year high school students, chosen based on their experience with the Rosetta Stone application for learning English. Data was collected using questionnaires and interviews. The questionnaire items were focused on  students’ motivation in using Rosseta Stone, improved English skill and confidence level after using the application. It was found that 50% of participants used the Rosetta Stone aplication to help them with their English at school. It's interesting to note that 10 out of 20 students (or 50%) said that after utilizing this application, their vocabularies abilities had improved the most. Additionally, according to 70% of respondents, utilizing the media improved users' English proficiency, with 8 out of 20 participants rating their degree of confidence in their ability to speak English as being a 5 on a scale of 5. Thus, Rosetta Stone application has been able to increase students' vocabulary mastery.